(1053) Some Ideas Concerning Aims, Tasks, and Principles of Organization of Spatial Planning بعض الأفكار المتعلقة بالأهداف والمهام ومبادئ تنظيم التخطيط المكانى - Siegfried Voigtsberger.. (INP, 2020)
Aims, tasks and principles of organization of spatial planning are part and parcel of the social states economic policy. Therefore they can`t exist independently, but only within the framework of overall national planning as an integral part of states state of planning system. Also, stressing the relationship means simultaneously, that spatial planning is an indispensable part of economic policy and planning, that plays a decisive role as instrument in social and economic development